Evaluation of stress intensity factors under multiaxial and compressive conditions using low order displacement or stress field fitting. (15th February 2018) - Andersson, Robin; Larsson, Fredrik; Kabo, Elena
Highlights: SIFs are estimated by fitting a minimalistic ansatz to FE-approximations. Different modes are accurately distinguished during mixed mode loading. Accurate results are obtained even for the case of compressive loading. XFEM applicability decreases the meshing effort. Application example of a surface breaking RCF crack in a rail head. Abstract: A methodology for evaluation of stress intensity factors from the asymptotic displacement (or stress) fields at a crack front is proposed. The methodology strives to be of practical use in conjunction with commercial FE-codes, also when approaches such as XFEM are employed. To this end, the matching of the fields is carried out through a minimalistic, low order, ansatz of the displacement and stress fields. As demonstrated, the proposed methodology can deal with multiaxial loading of curved crack fronts in three-dimensional bodies. The methodology shows good accuracy also for compressive loading when crack face friction can be neglected.